PENGHILANGAN POLUTAN ORGANIK DAN PADATAN TERRSUSPENSI DI DALAM AIR LIMBAH DOMESTIK DENGAN PROSES MOVING BED BIOFILM REACTOR (MBBR) - Said, Nusa Idaman; Santoso, Teguh Iman (Jurnal Air Indonesia, 2015)
One of the alternative technologies that could be used for domestic waste water treatment is the Moving Bed Biofilm Reactor (MBBR). MBBR in principle is activated sludge that is increased by adding media in to the reactor, so there are two treatments process happened inside, suspended growth and attached growth. This research is using bioball as a media which has surface area of ±210 m2/m3 by 20% volume of reactor volume. Wastewater treatment by MBBR uses variations of Hydraulic Retention time (HRT) 12, 8, 6, and 4 hours, then the parameters measured were BOD, COD, TSS, temperature, and pH. Result of the study shows that within HRT for 12 hours in aeration tank, removal efficiency of COD is 81,37%, BOD is 82,4%, and TSS is 90,05%. HRT for 8 hours, COD removal efficiency is 88,72%, BOD is 89,7%, and TSS is 92,06%. HRT for 6 hours, COD removal efficiency is 85,48%, BOD is 80,15%, and TSS is 94,85%. HRT for 4 hours, COD removal efficiency is 81,07%, BOD is 87,88%, and TSS is 94,86%. With a retention time of 4 hours, the effluent results domestic wastewater treatment using MBBR has met quality standards in accordance with KEPMEN LH no. 112 of 2003 on Domestic Wastewater Quality Standard and Jakarta Governor Regulation no. 122 of 2005 on Domestic Wastewater Management in Special Province of Jakarta. Keywords: Domestic wastewater, MBBR, bioball.